A Theoretical Evaluation of Different Faces of Power: US-Turkey Relations Towards Iraq - Sözen, Ahmet (Uluslararası İlişkiler Konseyi Derneği, 2010)
Th is paper focuses on the use of diff erent forms of power by a (leader/patron/hegemonic) state to get the other (non-leader/client) states to cooperate with its policies. Most of the literature on cooperation operates on the level of bargaining power where the policy changes are directly visible. Th is article aims to show how the bargaining power model is not adequate in capturing the complete picture of the relationship between Turkey (a non-leader/client state) and the United States (leader/patron state) in their cooperation with regard to Iraq during the Gulf Crisis (1990) and the War against Iraq (2003). Hence, I attempt to show that the three levels of power as discussed by Krause is a better and more comprehensive framework for understanding and explaining the power relationship between Turkey and the US.
The file in this item is the publisher version (published version) of the article.
Keywords: Turkey; Iraq; Bargaining Power; Structural Power; Hegemonic Power